PENCEGAHAN KEJADIAN DEKUBITUS DENGAN PENGGUNAAN HEEL RING PADA PASIEN YANG TERPASANG TRAKSI SKELETAL - Asri Fatonah; Sriyono Sriyono; Deni Yasmara (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: The decubitus on the heel area can impact to the users of traction skeletal in patients with musculoskeletal injuries. The position of prolonging elevation and pressure make poor vascular circulation flow. The use of heel ring can reduce the pressure and static resistance. The purpose of this study was to determine the effect of the heel ring on the incidence of decubitus in patients with skeleton traction installed in the Bedah Flamboyan Ward, Dr. Soetomo Hospital, Surabaya.Methods: A pre-experimental with one group pre-post test design was used in this study. The population in this study were patients with skeleton traction installed of Bohler Braun frame. There were 14 samples who met the inclusion criteria. The independent variable was heel ring and the dependent variable was the incidence of decubitus. Data was collected using observation sheet of incidence of decubitus then analyzed using with Wilcoxon Signed Rank Test with significance level <0.05.Results: Almost half (35.71%) encounter level 1of decubitus before using the heel ring, and 100% no incidence of decubitus after use the heel ring. The result showed that there was an effect after the use of heel ring to the incidence of decubitus with p=0.025.Conclusion: The heel ring can be prevented decubitus in patients with traction skeleton. The result of this study can be a reference for standardizing the operating procedure, especially for the patient's traction skeleton.